2021
DOI: 10.3390/mi12010084
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots: An Emerging Smart Material for Analytical Applications

Abstract: Carbon dots (CDs) are optically active carbon-based nanomaterials. These nanomaterials can change their light emission properties in response to various external stimuli such as pH, temperature, pressure, and light. The CD’s remarkable stimuli-responsive smart material properties have recently stimulated massive research interest for their exploitation to develop various sensor platforms. Herein, an effort has been made to review the major advances made on CDs, focusing mainly on its smart material attributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 190 publications
0
58
0
1
Order By: Relevance
“…The enhancement in QY is possibly because nitrogen‐containing groups are good electron donors and can introduce electronic states that are more favorable for radiative decay [54–55] . Furthermore, it was previously found that the nitrogen‐containing groups could act as surface passivating agents, which trapped surface electrons for more efficient radiative recombination, thus considerably enhancing the photoluminescence in N‐CDs [56–60] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement in QY is possibly because nitrogen‐containing groups are good electron donors and can introduce electronic states that are more favorable for radiative decay [54–55] . Furthermore, it was previously found that the nitrogen‐containing groups could act as surface passivating agents, which trapped surface electrons for more efficient radiative recombination, thus considerably enhancing the photoluminescence in N‐CDs [56–60] …”
Section: Resultsmentioning
confidence: 99%
“…[54][55] Furthermore, it was previously found that the nitrogen-containing groups could act as surface passivating agents, which trapped surface electrons for more efficient radiative recombination, thus considerably enhancing the photoluminescence in N-CDs. [56][57][58][59][60] From these results, we can conclude that photoluminescence of CDs from table sugar can be tuned by heteroatom doping. All CDs exhibited excitation-dependence photoluminescence (Figure S2).…”
Section: Fluorescence Emissionmentioning
confidence: 90%
“…The chemical property of CQD is highly important among all the properties due to their photoluminescence phenomenon, chirality and UV-absorption [122]. Typically, CDs can act as both electron acceptors and donors [123]. All these properties are discussed below in detail by citing relevant literature.…”
Section: Properties Of Cqdsmentioning
confidence: 99%
“…Although using excellent properties such as low toxicity [140] and good biocompatibility makes CQDs ideal materials for bioimaging, biosensors and drug delivery applications, CQDs can, however, offer advantages in catalysis, sensors and optronics based on their excellent optical and electronic properties [123].…”
Section: Emerging Applications Of Carbon Dotsmentioning
confidence: 99%
See 1 more Smart Citation